2008
DOI: 10.2133/dmpk.23.421
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Induction of Rat Hepatic CYP1A1 and CYP1A2 Expression after Single-dose Administration of the Anti-angiogenic Agent TSU-68

Abstract: The anti-angiogenic agent TSU-68 is known to rapidly induce cytochrome P450 activity responsible for its own hydroxylation in rats. In this study, we identified CYP1A1 and CYP1A2 as the TSU-68-induced P450 and temporally characterized the rapid induction of these isoforms. Protein and mRNA levels of CYP1A1 and CYP1A2 along with CYP1A activities were examined in rat liver after a single oral administration of 500 mg/kg TSU-68. CYP1A-mediated ethoxyresorufin O-deethylation and TSU-68 hydroxylation activities rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A 24-h-treatment period was used in this study, because it was found to be an appropriate length of time to observe protein induction by several inducers [59,[63][64][65]. The increase in CYP1A1 protein levels and enzyme activities reached a maximum at 12-20 h and then remained constant up to 24 h after treatment with a single dose of inducers before slowly dropping to background levels [59,[63][64][65]. In contrast, CYP1A1 mRNA reached its highest level as early as 3-5 h [65][66][67][68][69].…”
Section: The Effect Of 3-aba Pretreatment On Activation Of 3-aba By Rmentioning
confidence: 99%
“…A 24-h-treatment period was used in this study, because it was found to be an appropriate length of time to observe protein induction by several inducers [59,[63][64][65]. The increase in CYP1A1 protein levels and enzyme activities reached a maximum at 12-20 h and then remained constant up to 24 h after treatment with a single dose of inducers before slowly dropping to background levels [59,[63][64][65]. In contrast, CYP1A1 mRNA reached its highest level as early as 3-5 h [65][66][67][68][69].…”
Section: The Effect Of 3-aba Pretreatment On Activation Of 3-aba By Rmentioning
confidence: 99%
“…Some drugs, such as dasatinib, nicotine, TSU-68, insulin, can induce the expression or activity of CYP1A1 (Kitamura et al. 2008 ; Wang et al. 2009 ; Alsaad 2018 ; Kuzgun et al.…”
Section: Discussionmentioning
confidence: 99%
“…When the effect of TSU-68 on both the ORR and adverse events is considered, it can be said that TSU-68 decreases the efficacy of SOX treatment. TSU-68 is thought to induce CYP1A1 and 1A2 [21], while FT, the main compound of S-1, is mainly metabolized by CYP2A6 [22]. Since CYP1A1 and CYP1A2 can metabolize FT, a potential drug interaction between TSU-68 and S-1 may influence the efficacy of the TSU-68+SOX combination.…”
Section: Discussionmentioning
confidence: 99%